Group portrait of the attendees of the 6th Methodist's Layman's Retreat in Mission Springs, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the 6th Methodist's Laymen's Retreat in Mission Springs, California. The photograph of the all-male group was taken outside of an unidentified building.